THE IMPORTANT OF CREATIVE THINKING ABILITY IN ELEMENTARY SCHOOL STUDENTS FOR 4.0 ERA - Astuti, Astuti; Waluya, St Budi; Asikin, Mohammad (Universitas Ahmad Dahlan, 2020)
The art of creative thinking needs to develop and taught to students because by thinking creativity, students are able to solve the problem they have, the students become more independent, creating reliable and talented human resources, and skillful in the future. The purpose of this research is to find out the creative thinking ability in the mathematic aspect of Elementary School Mardi Rahayu 02 Ungaran students. The data collection was done by giving four questions of students' creative thinking ability on KPK and FPB materials along with with interview the students. The research was done to 31 students of class IVC. The method used is qualitative descriptive method. Creative thinking ability is important in Era 4.0 where the development of knowledge becomes really fast. The average achievement of every creative thinking indicator is fluency 45,8% and flexibility 58,3%, whereas originality and elaboration indicator reaches 33,3%. The conclusion from this research is that the creative thinking ability of Elementary School Mardi Rahayu 02 Ungaran students need to improve